Antibacterial Potential of the Extracts of the Leaves of Azadirachta indica Linn. - Saradhajyothi KOONA; Subbarao BUDIDA (Notulae Scientia Biologicae, 2011)
Azadirachta indica A. Juss (syn. Melia azadirachta) is well known in India and popularly known as Indian neem. To evaluate antibacterial potential, the agar well diffusion assay was used against Gram-negative and Gram-positive bacteria. Penicillin and Dimethyl sulfoxide were used as positive and negative controls, respectively. Methanol extract showed the highest and chloroform extract showed moderate to good antibacterial activity. Proteus vulgaris and Micrococcus luteus were the most susceptible bacteria while Bacillus subtilis was more resistant bacterium to the hexane, chloroform and methanol extracts of neem. The study recommended for the isolation and separation of bioactive compounds responsible for the antibacterial activity.